Comparison of the Analgesic Effects of Pulse Radiofrequency and Cryoablation in Rabbits with Mental Nerve Neuropathic Pain - KÜTÜK, NÜKHET; Canpolat, D. G.; SOYLU, EMRAH; DOĞRUEL, FATMA; Kutuk, Nükhet; UĞUR, FATİH (My University, 2018)
Purpose: After mental nerve injury, several sensory disorders may occur. The alterations in sensation may differ from mild paresthesia to complete anesthesia, or neuropathic pain. Neuropathic pain is a difficult clinical condition to manage. The aim of this study was to compare the analgesic effects of pulsed radiofrequency (PRF) and cryoablation in an experimental mental nerve neuropathic pain model in rabbits. Materials and Methods: Fifteen rabbits were divided into three groups. One-third to one-half of the mental nerve was ligated with 4-0 silk sutures. In Group 1, a nonconducting PRF electrode was placed on the mental nerve for 6 min, whereas the mental nerve was exposed to PRF in Group 2. In Group 3, the cryoablation was processed. The responses to thermal and mechanical stimuli were measured at the 1st, 2nd, 3rd, and 4th weeks. Results: There were no statistically significant differences among the groups for thermal withdrawal latency to heat stimulation in any weeks (P > 0.05). However, a significant difference was found between the groups (P < 0.05) in the 3rd and 4th weeks for mechanical withdrawal latency values. Conclusions: Both PRF and cryoablation therapies are successful in the treatment of experimentally induced mental nerve neuropathic pain in rabbits.